Bo – bowiem – albowiem. Między spójnikiem a partykułą - Kisiel, Anna (Forum Lingwistyczne, 2015)
Bo – bowiem – albowiem. Between a conjunction and a particle The article presents three etymologically related units: bo, bowiem i albowiem. Basing on analysis of the contexts of their use (requirement of a weaker / stronger pause, ability to cooperate with anelliptic sentence, possibility of changing position within a sentence), with particular regard to binding between a rheme of the sentence with which these units coocurate and a preceeding rheme, the possibility of including bowiem and albowiem into the classes of particles and conjunctions is discussed. Key words: particle, conjunction, connector